2022
DOI: 10.21037/jgo-22-542
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities and standard treatment in locally advanced rectal cancer: a National Cancer Database study

Abstract: Background: Mortality rates in colorectal cancer (CRC) continue to be higher in Black compared to White patients. While standard treatment modalities for locally advanced rectal cancer have been shown to improve outcomes, there are limited studies assessing the receipt of standard treatment in rectal cancer based on race. Therefore, we sought to evaluate the use of standard treatment across racial groups in locally advanced rectal cancer and its effect on survival. Methods: The National Cancer Database (NCDB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…15,16,23 When evaluating ethnicity descriptions available in surgical trials, 11 trials (73.3%) did not report the ethnicity of their participants. 3,14,[16][17][18][19][20][21][22][24][25][26] Two trials described ethnicity as "Caucasian/non-Caucasian, " 12,13 and only 2 trials reported 1 ethnicity as Hispanic (yes/no). 15,23 Only 2 studies (13.3%) had both racial and ethnic descriptions for all their participants.…”
Section: Race and Ethnicity Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16,23 When evaluating ethnicity descriptions available in surgical trials, 11 trials (73.3%) did not report the ethnicity of their participants. 3,14,[16][17][18][19][20][21][22][24][25][26] Two trials described ethnicity as "Caucasian/non-Caucasian, " 12,13 and only 2 trials reported 1 ethnicity as Hispanic (yes/no). 15,23 Only 2 studies (13.3%) had both racial and ethnic descriptions for all their participants.…”
Section: Race and Ethnicity Description Of Included Studiesmentioning
confidence: 99%
“…1 However, substantial evidence shows that certain racial and ethnic groups, such as Blacks and Hispanic Americans, are less likely to receive appropriate screening and timely treatment for CRC compared to non-Hispanic Whites. [2][3][4] Reports have shown that racial and ethnic minorities are also underrepresented in clinical trials. 5,6 Clinical trials are essential in advancing medical knowledge and improving patient outcomes, as they provide critical information on the safety and effectiveness of new treatments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 39 articles, 15 studies found that patients who identified as having Hispanic/Latinx ethnicity were significantly more likely to not receive radiation treatment 17,18,20,21,23,28,33,35,[39][40][41][42][43][44][45] for prostate cancer (n = 4 articles), glioblastoma (n = 2), breast cancer (n = 1), anaplastic thyroid cancer (n = 1), pancreatic cancer (n = 1), gynecologic cancer (n = 2), rectal cancer (n = 1), NSCLC (n = 1), and pediatric sarcoma (n = 1). In addition, 10 articles revealed that Hispanic patients are more likely to receive non-guideline-concordant care, 22,[46][47][48][49][50][51][52][53][54] and this was identified in prostate cancer (n = 2 articles), gynecologic cancer (n = 2), rectal cancer (n = 1), head and neck cancer (n = 1), lung (n = 1), sarcoma (n = 1), and glioblastoma (n = 1),…”
Section: Time To Treatment Initiation and Completionmentioning
confidence: 99%
“…Unfortunately, multiple patients are diagnosed with locally advanced CRC at the time of initial diagnosis (3,4). In such cases, neoadjuvant therapy plays a crucial role in providing patients with more opportunities for subsequent surgical resection and improving their long-term survival outcomes (5)(6)(7). Currently, the primary neoadjuvant regimen for patients with locally advanced CRC involves platinum-based chemotherapy, such as capecitabine plus oxaliplatin (XELOX) and fluorouracil (8,9).…”
Section: Introductionmentioning
confidence: 99%